Phosphate-chloride solid electrolyte as well as preparation method and application thereof
By introducing phosphate into the chloride solid electrolyte to form phosphate-chloride solid electrolyte with metal chloride and phosphate skeleton structure, the problems of low conductivity and high voltage instability of existing chloride electrolytes are solved, and a higher The lithium-ion conductivity and wider electrochemical window improve the performance and safety of solid-state batteries.
Patent Information
- Application Number
- CN202411566202.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing chloride solid electrolyte has low ion conductivity and is prone to oxidation and decomposition at high voltages, which limits the improvement of solid-state battery performance.
The phosphate-chloride solid electrolyte with metal chloride and phosphate as the framework structure is used to improve lithium ion conductivity and high voltage stability by adjusting chemical composition and ball milling conditions.
It significantly improves the conductivity of lithium ion, expands the electrochemical window, improves the performance and safety of solid-state batteries, and is suitable for high-energy density all-solid-state batteries.
Smart Images

Figure HDA0005119312230000011 
Figure HDA0005119312230000012 
Figure HDA0005119312230000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a phosphate-chloride solid electrolyte and a preparation method and application thereof. Background Art
[0002] As an electrochemical energy storage device, lithium-ion batteries have been widely used in new energy vehicles, digital products, mobile electronic devices and other fields due to their significant advantages of high energy density. People's requirements for the charging speed, life and safety of lithium-ion batteries are also increasing. Traditional lithium-ion battery electrolytes usually use flammable organic liquids as solvents, which are prone to problems such as interfacial gas production and thermal runaway during battery operation, resulting in battery life degradation and even safety accidents such as combustion and explosion. Using non-flammable solid electrolytes to replace liquid organic electrolytes as lithium ion conductive media can effectively improve the safety of lithium-ion batteries. At the same time, since solid-state batteries do not require the use of diaphragms and can use metal lithium negative electrodes, the energy density of the battery is expected to be further improved.
[0003] At present, the developed solid electrolytes include oxides, sulfides and halides. Among them, oxide electrolytes are not easy to deform and have poor contact with electrodes, which limits the lithium ion transmission at the interface. Sulfide electrolytes can form good interface contact with electrodes, but are easily oxidized under high voltages and cannot match the positive electrode materials. Chloride electrolytes can have both good interface contact and high-voltage stability, and are ideal materials for matching positive electrodes in solid-state batteries. However, the ionic conductivity of existing chloride solid electrolytes is still not high enough, and oxidative decomposition will still occur when the voltage is higher than 4.2V, which limits the further improvement of solid-state battery performance. Therefore, it is necessary to optimize the current chloride electrolytes and develop chloride solid electrolytes with higher ionic conductivity and better resistance to high pressure. Summary of the invention
[0004] In view of the defects of the prior art, the present invention provides a solid electrolyte with metal chloride and phosphate as the skeleton structure. The solid electrolyte improves the lithium ion conductivity of the existing chloride electrolyte, while improving its high voltage stability, matching the interface of the positive electrode material, thereby improving the performance of the all-solid-state battery.
[0005] The phosphate-chloride solid electrolyte provided by the present invention has a chemical formula as shown in formula (I):
[0006] MCl n ·xLi3PO4 / LiPO3·yLiCl(I)
[0007] Wherein, M is one or more of Zr, Hf, Nb, Ta, Mo, W, Re, Fe, Cu, Zn, Al, and In; 2≤n≤6; 0.1≤x≤1, 0≤y≤2; preferably, 0.2≤x≤0.6, 0.4≤y≤1.2
[0008] According to one embodiment of the present invention, the phosphate-chloride solid electrolyte has a chemical formula of:
[0009] ZrCl4·0.25LiPO3·1.6LiCl
[0010] The solid electrolyte of the present invention is Cl - PO4 3- Anion and M n+ Metal cations are the structural framework, and the ionic conductivity is greater than 1×10 -4 S / cm, and the electrochemical window is within 0~5V.
[0011] The present invention also provides a method for preparing the phosphate-chloride solid electrolyte.
[0012] The preparation method of the phosphate-chloride solid electrolyte provided by the present invention comprises the following steps: weighing and mixing metal chloride and phosphate according to the stoichiometric ratio of elements in the target solid electrolyte, and ball milling in a ball mill to obtain the result.
[0013] In the above preparation method, the raw materials used are: phosphate is Li3PO4 or / and LiPO3, metal chloride is LiCl and MCl n .
[0014] In the above preparation method, the ball milling conditions are as follows: the rotation speed is 300-1000 rpm, and the ball milling time is 10-100 h; preferably, the rotation speed is 400-600 rpm, and the ball milling time is 30-60 h.
[0015] In the above preparation method, all weighing, mixing and ball milling steps are carried out in an inert gas atmosphere, such as Ar, and the O2 and H2O contents are less than 0.01 ppm.
[0016] The phosphate-chloride solid electrolyte of the present invention can be applied to solid-state lithium-ion batteries.
[0017] Furthermore, the application is the application of the phosphate-chloride solid electrolyte in preparing the lithium ion transport medium of the solid-state battery.
[0018] Based on the above phosphate-chloride solid electrolyte, the present invention also provides a composite positive electrode material.
[0019] The composite positive electrode material is composed of the phosphate-chloride solid electrolyte and the positive electrode active material; or is composed of the phosphate-chloride solid electrolyte, the positive electrode active material and the conductive agent.
[0020] The positive electrode active material is LiCoO2, LiNiO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiFePO4, LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.92 Co 0.03 Mn 0.05 One or more of O2;
[0021] The conductive agent is one or more of conductive carbon black, Super-P, Ketjen black, acetylene black, and carbon nanotubes;
[0022] The mass ratio of the positive electrode active material, the phosphate-chloride solid electrolyte and the conductive agent in the composite positive electrode material is 60-90:10-40:0-10, preferably 70-80:20-30:0-5.
[0023] According to an embodiment of the present invention, the composite positive electrode is composed of positive electrode active material LiNi 0.92 Co 0.03 Mn 0.05 O2 and ZrCl4·0.3Li3PO4 solid electrolyte are mixed in a mass ratio of 70:30.
[0024] The invention also provides a method for preparing the composite positive electrode material, comprising the following steps: mixing the phosphate-chloride solid electrolyte, positive electrode active material and conductive agent in proportion and then grinding or ball milling the mixture.
[0025] Based on the above-mentioned phosphate-chloride solid electrolyte, the present invention also provides a solid-state battery that can be used for energy storage.
[0026] The solid-state battery comprises a positive electrode, a solid electrolyte and a negative electrode; the solid electrolyte is the phosphate-chloride solid electrolyte, or a combination of the phosphate-chloride solid electrolyte and the sulfide solid electrolyte, and the preferred mass ratio of the two is 1:1-3;
[0027] The material of the positive electrode is the composite positive electrode material;
[0028] The material of the negative electrode is one or more of metal Li, Li-In alloy, Si negative electrode, and graphite negative electrode.
[0029] The sulfide solid electrolyte is preferably Li6PS5Cl.
[0030] The present invention also provides a method for preparing the solid-state battery, comprising the following steps:
[0031] First, the solid electrolyte is pressed into a solid electrolyte sheet (such as a round sheet with a diameter of 10 mm), and then the composite positive electrode material is added to one side of the solid electrolyte sheet and pressurized (200-400 MPa) to form a positive electrode, and the negative electrode material is added to the other side and pressurized (50-150 MPa) to form a negative electrode. Finally, a certain pressure (10-150 MPa) is applied to assemble and obtain the solid-state battery.
[0032] In the above preparation method, all steps are carried out under the protection of an inert atmosphere, such as Ar, and the contents of O2 and H2O are both less than 0.01 ppm.
[0033] The present invention is based on the existing chloride solid electrolyte, by adding phosphate, to form a structure with metal ions M n+ With Cl - PO4 3- The network skeleton structure connected by the electrolyte provides a class of solid electrolyte materials with considerable ion conductivity (ionic conductivity>10 -4 S / cm), and on the other hand, it can further improve the high-voltage stability of chloride electrolyte to positive electrode materials (>4.5V). The preparation method of the present invention is simple to operate, the product performance is easy to control, and it is convenient for large-scale production, which is conducive to promoting the development and progress of solid-state battery related industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the EIS test result of the phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4 in Example 1.
[0035] Figure 2 This is the XRD test result of the phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4 in Example 1.
[0036] Figure 3 This is the SEM image of the phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4 in Example 1.
[0037] Figure 4 This is the EIS test result of the phosphate-chloride solid electrolyte ZrCl4·0.25LiPO3·1.6LiCl in Example 2.
[0038] Figure 5 This is the XRD test result of the phosphate-chloride solid electrolyte ZrCl4·0.25LiPO3·1.6LiCl in Example 2.
[0039] Figure 6 This is the SEM image of the phosphate-chloride solid electrolyte ZrCl4·0.25LiPO3·1.6LiCl in Example 2.
[0040] Figure 7 These are the electrochemical test results of the phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4 in Example 7. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0042] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0043] Example 1. Preparation and performance testing of phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4
[0044] 1. Preparation of phosphate-chloride solid electrolyte
[0045] In an argon glove box, accurately weigh ZrCl4 and Li3PO4 into a ball mill with a molar ratio of 1:0.3. Add zirconium oxide ball milling beads with a mass 20 times the total mass of the raw materials, seal the ball mill well, and protect the ball mill with argon atmosphere. Ball mill at a speed of 550 rpm for 50 hours to obtain phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4.
[0046] 2. Test of lithium ion conductivity
[0047] The prepared electrolyte powder was placed in a polytetrafluoroethylene mold with a diameter of 10 mm, and then the electrolyte powder was pressed into a tablet using an iron cylinder with a diameter of 10 mm at a pressure of 5.5 t. After sealing, the electrochemical impedance test was performed. The test results are shown in Figure 2. Figure 1 As shown, the ionic conductivity at room temperature is 6.6×10 -4 S cm -1 .
[0048] 3. Phase Characterization of Phosphate-Chloride Solid Electrolyte
[0049] The electrolyte powder was subjected to XRD and SEM tests under anhydrous and O2-free conditions. The test results are as follows Figure 2 , Figure 3 shown.
[0050] Example 2. Preparation and performance testing of phosphate-chloride solid electrolyte ZrCl4·0.25LiPO3·1.6LiCl
[0051] 1. Preparation of phosphate-chloride solid electrolyte
[0052] The preparation steps are basically the same as those in Example 1, except that the raw materials are ZrCl4, LiPO3, and LiCl weighed in a molar ratio of 1:0.25:1.6.
[0053] 2. Test of lithium ion conductivity
[0054] The test conditions are basically the same as those in Example 1, and the test results are as follows: Figure 4 As shown, the ionic conductivity at room temperature is 7.3×10 -4 S cm -1 .
[0055] 3. Phase Characterization of Phosphate-Chloride Solid Electrolyte
[0056] The electrolyte powder was subjected to XRD and SEM tests under the same test conditions as in Example 1. The test results are shown in FIG. Figure 5 , Figure 6 shown.
[0057] Example 3. Preparation and performance testing of phosphate-chloride solid electrolyte TaCl5·0.4Li3PO4
[0058] 1. Preparation of phosphate-chloride solid electrolyte
[0059] The preparation steps are basically the same as those in Example 1, except that the raw materials are TaCl5 and Li3PO4 weighed in a molar ratio of 1:0.4.
[0060] 2. Test of lithium ion conductivity
[0061] The test conditions are basically the same as those in Example 1. The ionic conductivity at room temperature obtained by the test is 1.2×10 -4 S cm -1 .
[0062] Example 4. Preparation and performance test of phosphate-chloride solid electrolyte TaCl5·0.6Li3PO4·0.2LiCl 1. Preparation of phosphate-chloride solid electrolyte
[0063] The preparation steps are basically the same as those in Example 1, except that the raw materials are TaCl5, Li3PO4, and LiCl weighed in a molar ratio of 1:0.6:0.2.
[0064] 2. Test of lithium ion conductivity
[0065] The test conditions are basically the same as those in Example 1. The ionic conductivity at room temperature obtained by the test is 2.9×10 -4 S cm -1 .
[0066] Example 5. Preparation and performance testing of phosphate-chloride solid electrolyte NbCl5·0.5Li3PO4
[0067] 1. Preparation of phosphate-chloride solid electrolyte
[0068] The preparation steps are basically the same as those in Example 1, except that the raw materials are NbCl5 and Li3PO4 weighed in a molar ratio of 1:0.5.
[0069] 2. Test of lithium ion conductivity
[0070] The test conditions were basically the same as those in Example 1. The ionic conductivity at room temperature was 1.7×10 -4 S cm -1 .
[0071] Example 6. Preparation and performance testing of phosphate-chloride solid electrolyte NbCl5·0.35Li3PO4·0.4LiCl
[0072] 1. Preparation of phosphate-chloride solid electrolyte
[0073] The preparation steps are basically the same as those in Example 1, except that the raw materials are NbCl5, Li3PO4, and LiCl weighed in a molar ratio of 1:0.35:0.4.
[0074] 2. Test of lithium ion conductivity
[0075] The test conditions are basically the same as those in Example 1. The ionic conductivity at room temperature obtained by the test is 2.1×10 -4 S cm -1 .
[0076] Example 7: Electrochemical test of phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4
[0077] 1. Preparation of composite cathode materials
[0078] The positive electrode active material LiNi 0.92 Co 0.03 Mn 0.05O2 and phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4 were weighed in a mass ratio of 70:30, mixed in an agate mortar, and ground for 30 minutes to mix the materials evenly, thereby obtaining a composite positive electrode material.
[0079] 2. Assembly of all-solid-state batteries
[0080] First, 70 mg of sulfide solid electrolyte Li6PS5Cl was added to a mold with a diameter of 10 mm and pressurized for 1 t, followed by 30 mg of phosphate-chloride solid electrolyte ZrCl4·0.3Li3PO4 and pressurized for 1 t. Then, 8 mg of composite positive electrode material was added to the positive electrode side (the side in contact with ZrCl4·0.3Li3PO4) and pressurized for 3 t, and Li-In alloy was added to the negative electrode side (the side in contact with Li6PS5Cl) and pressurized for 1.5 t. All the above processes were carried out in an Ar atmosphere glove box.
[0081] 3. Testing of all-solid-state batteries
[0082] The test temperature is 25°C, the voltage range of the constant current charge and discharge test is 2.4~3.9V (vs.Li-In), and the charge and discharge curve of the all-solid-state battery at a rate of 0.1C is as follows Figure 7 As shown, the discharge specific capacity of the battery is 187 mAh / g.
[0083] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.
Claims
1. A solid electrolyte based on metal chloride and phosphate, whose chemical formula is shown in formula (I): MCl n ·xLi3PO4 / LiPO3·yLiCl(I) in, M is one or more of Zr, Hf, Nb, Ta, Mo, W, Re, Fe, Cu, Zn, Al, and In; 2≤n≤6; 0.1≤x≤1, 0≤y≤2.
2. The solid electrolyte based on metal chloride and phosphate according to claim 1, characterized in that: 0.2≤x≤0.6, 0.4≤y≤1.
2.
3. The method for preparing a solid electrolyte based on metal chloride and phosphate according to claim 1 or 2, comprising the following steps: weighing and mixing the metal chloride and phosphate according to the stoichiometric ratio of the elements in the target solid electrolyte, and ball milling them in a ball mill.
4. The preparation method according to claim 3, characterized in that: The phosphate is Li3PO4 or LiPO3, and the metal chloride is LiCl and MCl. n ; And / or, the rotation speed of the ball mill is 300-1000 rpm, and the ball milling time is 10-100 h; preferably, the rotation speed is 400-600 rpm, and the ball milling time is 30-60 h; And / or, the weighing, mixing and ball milling steps are all carried out in an inert gas atmosphere, and the O2 and H2O contents are both less than 0.01 ppm.
5. Use of the solid electrolyte based on metal chloride and phosphate according to claim 1 or 2 in the preparation of solid-state batteries; Furthermore, the application is the use of the solid electrolyte based on metal chloride and phosphate in the preparation of the lithium ion transport medium of the solid-state battery.
6. A composite positive electrode material, consisting of the solid electrolyte based on metal chloride and phosphate, a positive electrode active material and a conductive agent as claimed in claim 1 or 2, or consisting of the solid electrolyte based on metal chloride and phosphate, a positive electrode active material as claimed in claim 1 or 2.
7. The composite positive electrode material according to claim 6, characterized in that: The positive electrode active material is LiFePO4, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.92 Co 0.03 Mn 0.05 One or more of O2; And / or, the conductive agent is one or more of conductive carbon black, Super-P, Ketjen black, acetylene black, and carbon nanotubes; And / or, the mass ratio of the solid electrolyte based on metal chloride and phosphate, the positive electrode active material and the conductive agent is 60-90:10-40:0-10, preferably 70-80:20-30:0-5.
8. A solid-state battery, comprising a positive electrode, a solid electrolyte and a negative electrode, characterized in that: The solid electrolyte comprises the solid electrolyte based on metal chloride and phosphate according to claim 1 or 2.
9. The solid-state battery according to claim 8, characterized in that: The solid electrolyte is the solid electrolyte based on metal chloride and phosphate, or a combination of the solid electrolyte based on metal chloride and phosphate and a sulfide solid electrolyte. Preferably, the mass ratio of the solid electrolyte based on metal chloride and phosphate to the sulfide solid electrolyte is 1:1-3; And / or, the material of the positive electrode is the composite positive electrode material according to claim 6 or 7; And / or, the material of the negative electrode is one or more of metal Li, Li-In alloy, Si negative electrode, and graphite negative electrode.
10. The method for preparing a solid-state battery according to claim 8 or 9, comprising the following steps: first, pressing the solid electrolyte into a solid electrolyte sheet, then adding the composite positive electrode material to one side of the solid electrolyte sheet and pressurizing it to form a positive electrode, and adding the negative electrode material to the other side and pressurizing it to form a negative electrode, to obtain the solid-state battery.